Lipid Histiocytosis of the Gallbladder Neck Lymph Node. (26th October 2016) - Handra-Luca, Adriana; Ben Romdhane, Mohamed Habib; Straub, Beate Katharina
Abstract : Lipid histiocytosis of the gallbladder neck lymph node is rarely reported nowadays. Two obese patients presented with gallbladder lithiasis detected on CT scan. The treatment consisted in coelioscopic cholecystectomy. Microscopy revealed subacute/chronic lithiasic cholecystitis and foci of vacuolated cells in the gallbladder neck lymph node. These cells were positive for CD68, CD31, S100 protein, and adipophilin and negative for cytokeratin and Alcian blue. In conclusion, we report lymph node lipid histiocytosis diagnosed microscopically after cholecystectomy. While such lesions may remain unidentified on imaging procedures, the microscopic analysis may require special stains and immunohistochemistry for ruling out adenocarcinoma metastasis.